2011
DOI: 10.1111/j.1460-9568.2011.07936.x
|View full text |Cite
|
Sign up to set email alerts
|

Projections and interconnections of genetically defined serotonin neurons in mice

Abstract: Brain serotonin neurons are heterogeneous and can be distinguished by several anatomical and physiological characteristics. Toward resolving this heterogeneity into classes of functional relevance, subtypes of mature serotonin neurons were previously identified based on gene expression differences initiated during development in different rhombomeric (r) segments of the hindbrain. This redefinition of mature serotonin neuron subtypes based on the criteria of genetic lineage, along with the enabling genetic fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
171
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 35 publications
6
171
0
1
Order By: Relevance
“…We directly tested this by measuring the electrophysiological properties of the serotonergic raphe neurons in both the lateral wings (lwDR) and ventromedial (vmDR) aspect of the dorsal raphe in WT and KD animals as adults. We examined both of these subfields, because we previously found differences in their cell parameters (Crawford et al, 2010) and because they are known to have different projections, with the vmDR sending axons to forebrain structures such as the amygdala, medial prefrontal cortex, and caudate-putamen (Bang et al, 2012;Lowry et al, 2008;Michelsen et al, 2008), whereas the lwDR projects to sympathomimetic nuclei (Hale and Lowry, 2011;Johnson et al, 2004). We found that post-natal knockdown of receptors led to long-lasting changes in several of the membrane characteristics of the neurons, the sum of which resulted in increased cell excitability ( Figure 5).…”
Section: -Ht1a Autoreceptor Knockdown Has a Long-lasting Impact On Smentioning
confidence: 99%
“…We directly tested this by measuring the electrophysiological properties of the serotonergic raphe neurons in both the lateral wings (lwDR) and ventromedial (vmDR) aspect of the dorsal raphe in WT and KD animals as adults. We examined both of these subfields, because we previously found differences in their cell parameters (Crawford et al, 2010) and because they are known to have different projections, with the vmDR sending axons to forebrain structures such as the amygdala, medial prefrontal cortex, and caudate-putamen (Bang et al, 2012;Lowry et al, 2008;Michelsen et al, 2008), whereas the lwDR projects to sympathomimetic nuclei (Hale and Lowry, 2011;Johnson et al, 2004). We found that post-natal knockdown of receptors led to long-lasting changes in several of the membrane characteristics of the neurons, the sum of which resulted in increased cell excitability ( Figure 5).…”
Section: -Ht1a Autoreceptor Knockdown Has a Long-lasting Impact On Smentioning
confidence: 99%
“…The largest population of relaxin-3 expressing neurons is located within the tegmental area known as the nucleus incertus (NI), and these neurons project broadly throughout the brain [15][16][17][18][19]. The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25]. Anatomical and functional data [15][16][17][18] suggest that relaxin-3/RXFP3 systems may interact directly with monoamine [19,26] and other peptide systems [27][28][29], and/or act at shared downstream limbic and hypothalamic target areas to modulate 'anxiety' and other stress-related responses [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Only those cells that have expressed both recombinases will express the marker encoded by the indicator allele. Additionally, some indicator alleles encode a second marker designed to label the subtractive population (Awatramani et al, 2003;Bang et al, 2012;Farago et al, 2006;Jensen et al, 2008;Yamamoto et al, 2009). The subtractive population consists of the balance of cells defined by one of the gene expression domains, minus the intersectional population (Farago et al, 2006).…”
Section: Introductionmentioning
confidence: 99%